Penanaman Nilai-Nilai Keagamaan di Raudhatul Athfal Al Falah 2 Danakerta - Suprihatin Suprihatin (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2022)
This study aims to describe the implementation and methods used in instilling religious values ​​at RA Al Falah 2 Danakerta. This research is a qualitative descriptive study. The subjects of this study were homeroom teachers, madrasa heads and students of RA Al Falah 2 Danakerta. Data collection techniques in the form of observation, interviews and documentation. Data analysis techniques use the Miles & Huberman model: data reduction, data presentation, and reasoning. The results of the study show that: (1) The inculcation of religious values ​​at RA Al Falah 2 Danakerta is carried out through an activity management process which includes the Annual Program (PROTA), the Semester Program (PROSEM), The Weekly Learning Implementation Plan (RPPM) and the Daily Learning Implementation Plan (RPPH). The implementation of these activities includes opening activities, core activities, and closing activities. (2) The methods used in instilling religious values ​​at RA Al Falah 2 Danakerta include habituation methods, exemplary methods, demonstration methods, question and answer methods, play methods, storytelling methods, and field trip methods.